2013
DOI: 10.5005/jp-journals-10031-1037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tobacco Habits and Attitude toward Its Cessation among Outpatients of Mahatma Gandhi Mission's Dental College and Hospital, Navi Mumbai, Maharashtra

Abstract: Background Information regarding the tobacco habits in patients visiting Mahatma Gandhi Mission's (MGM) Dental College and Hospital is scarce. Therefore, development and better implementation of the tobacco cessation initiatives can be undertaken with the knowledge of the tobacco use among patients. Materials and Methods A cross-sectional, questionnairebased study was conducted among the outpatients of MGM Dental College and Hospital from July to September, 2012. Questions regarding the form of tobacco used,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…71% of the youths chewed gutkha on daily basis and 40% participants chewed 5-10 packets of gutkha daily, other studies have also reported that gutkha chewing was most common on a daily basis. 7,12 71% had been chewing gutkha for more than 3 years. Most of them consumed gutkha after meals and eventually they would spit out the gutkha.…”
Section: Discussionmentioning
confidence: 99%
“…71% of the youths chewed gutkha on daily basis and 40% participants chewed 5-10 packets of gutkha daily, other studies have also reported that gutkha chewing was most common on a daily basis. 7,12 71% had been chewing gutkha for more than 3 years. Most of them consumed gutkha after meals and eventually they would spit out the gutkha.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Consumption of the SLT products increases the risk of tooth decay, tooth loss, gum disease, lips and tongue cancer, stomach ulcers, depression, cardiovascular diseases, premature birth, low-birth weight, congenital iron deficiency anemia, infertility, as well as esophageal and pancreatic cancers. [ 5 6 7 8 ] A review of studies from 113 countries revealed that SLT products use alone accounts for loss of over 6 million disability-adjusted-life-years and has caused 266,592 deaths from cancers and heart disease. [ 9 ] Almost 85% of the global disease burden of SLT use is from the South Asia region, of which India accounts for 74% and Bangladesh accounts for 5%.…”
Section: Introductionmentioning
confidence: 99%
“…Many people who use smokeless tobacco may think that consuming these products is safer than smoking cigarettes, but all smokeless tobacco products contain toxic substances, and the use of smokeless tobacco poses a serious health risk (2). The use of smokeless tobacco products increases the risk of tooth decay and esophageal and pancreas cancer (3) and can also cause tooth stain, tooth loss, gum disease, lip and tongue cancer, gastric ulcer, depression, increased risk of cardiovascular diseases, premature birth, low birth weight, congenital iron deficiency anemia and infertility (3)(4)(5)(6)(7)(8)(9)(10). Although the consumption of all tobacco products is addictive, the amount of nicotine absorbed from smokeless tobacco is three to four times more than that from cigarettes (11).…”
Section: Introductionmentioning
confidence: 99%